Self on audio - Self, Douglas (Newnes, 2006)
Whether you are a dedicated audiophile who wants to gain a more complete understanding of the design issues behind a truly great amp, or a professional electronic designer seeking to learn more about the art of amplifier design, there can be no better place to start than with the 35 classic magazine articles collected together in this book. Douglas Self offers a tried and tested method for designing audio amplifiers in a way that improves performance at every point in the circuit where distortion can creep in – without significantly increasing cost. Through the articles in this book, he takes readers through the causes of distortion, measurement techniques, and design solutions to minimise distortion and efficiency. Most of the articles are based round the design of a specific amplifier, making this book especially valuable for anyone considering building a Self amplifier from scratch. Self is senior designer with a high-end audio manufacturer, as well as a prolific and highly respected writer. His career in audio design is reflected in the articles in this book, originally published in the pages of Electronics World and Wireless World over a 25 year period. An audio amp design cookbook, comprising 35 of Douglas Self's definitive audio design articles Complete designs for readers to build and adapt An anthology of classic designs for electronics enthusiasts, Hi-Fi devotees and professional designers alike.